A Prospective Observational Study to Establish a Correlation Between Tinnitus and Hearing Loss - Anshu Chopra; Madhurima Bannerjee; Sanjoy Ghosh (Bengal Journal of Otolaryngology and Head Neck Surgery)
Introduction: The prevalence of tinnitus in adults with hearing problems is very high (59 - 86%). Both tinnitus and sensorineural hearing loss can occur when there is damage throughout the auditory pathway from the inner ear to auditory cortex. Our aim of the study was to evaluate the prevalence of hearing loss in patients with tinnitus and to assess the association between tinnitus and hearing loss.